3)(5х+-6)([+6)+13х=0 -7)2-7(7-4х)=0 -5)2+5(2х-1)=0

emerenkova1 emerenkova1    3   31.03.2019 10:20    0

Ответы
akalitp08ipr akalitp08ipr  27.05.2020 21:46

1) опечатка, исправь

2) перемножаешь и получаешь

32x=63

x=63/32

 

3) так же перемножаешь и получаешь

12х=15

х=5/4

ПОКАЗАТЬ ОТВЕТЫ
hgfgff1Fgfh hgfgff1Fgfh  27.05.2020 21:46

1) (2х-3)(5х+1)-(х-6)(x+6)+13х=0

10x^2 + 2x- 15x- 3- x^2 + 36 + 13x =0

9x^2 +33 =0

9x^2=-33

3x^2=-11

 

2) (2х-7)2-7(7-4х)=0

8x-14-49+28x=0

32x=63

 x=63/32

x=одна целая 31/32

 

3)(х-5)2+5(2х-1)=0

2x-10+10x-5=0

12x=15

4x=5

x=5/4

x=одна целая 1/4

 

ПОКАЗАТЬ ОТВЕТЫ